4. Implementing the Concept of Artistic Efficiency: Some Sugestions for Teachers - Bularga Tatiana (Sciendo, 2023)
In efforts to design the implementation process of innovative artistic praxeology we emerged from the assumption that TDA (teacher's didactic action) and PAA (pupil artistic action) become fundamental values of the integration of theory and praxeology in perspective of an effective education, provided that they be widely used both horizontally and vertically, according to the pentagonal model consisting of principles: proactivity, artistic intro-opening, creation/creativity, of success, re-conceptualizing and instrumented in modern theoretical and methodological perspectives.